Pengaruh Waktu dan Cara Pemberian N sebagai Pupuk Tambahan terhadap Pertumbuhan dan Hasil Kedelai (Glycine Max (L.) Merr.) pada Budidaya Basah - Sri Mulatsih; Wahju Q. Mugnisjah; Didy Sopandie; Komaruddin Idris (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2000)
An experiment was conducted at Muara Experimental Station, Research Institute of Food Crops Biotechnology, Bogor, from October 1996 to January 1997. Split block design was used in this experiment. Factors of experiment consisted of time of fertilizer application (3 week after planting (wap), 3 and 5 wap, and 3, 5, and 7 wap) and method of N fertilizer application (100% fertilizer through soil; 75% through soil, 25% through leaves; 50% through soil, 50% through leaves; 25% through soil, 75% through leaves; and 100% through leaves). Result of experiment showed that N application at 3 and 5 wap with 50% through soils and 50% through leaves increased dry weight to 11.4% if compared to 100% N through foliar application. Time of N application to 7 wap increased empty pod/plant to 31%. Method of N fertilizer application through leaves damaged the soybean leaves.   Key word: Fertilization, Nitrogen, Soybean